Then and Now: Depicting a Changing National Profle of STEM Career and Technical Education Course Takers. Issue 2 (February 2020) - Plasman, Jay Stratte; Gottfried, Michael A.; Hutt, Ethan L.
Background: After nearly a century of federal policies focusing on career-related high school coursework, a 2006 policy reauthorization especially called for increased rigor in STEM-themed career and technical education (CTE) courses and increased participation from all students, and particularly women and those with disabilities. We explore whether this reauthorization helped meet these calls for increased participation. Research Questions: We asked the following research questions in exploring the implementation of the Perkins IV act: (1) How have the predictors of participation in AS-CTE coursework changed during the decade between 2004 and 2013? (2) Were students in the class of 2013 more likely to participate in AS-CTE than those in the class of 2004? (3) Is there a specific difference in AS-CTE participation for female students and students with disabilities in the class of 2013 as compared to the class of 2004? Research Design: To respond to these questions, we merged two nationally representative datasets—the Education Longitudinal Study of 2002 (ELS:2002) and the High School Longitudinal Study of 2009 (HSLS:2009). We employed basic logistic regression to explore changes in participation and ordinary least squares regression to explore changes in credit accumulation. We also utilized double hurdle and state fixed-effects models to account for various potential biases. Results: We found that there were slight changes in predictors of applied STEM CTE course-taking, though female students remained significantly less likely than male students to participate in each cohort. Exploring across cohorts, we found students in the later cohort (HSLS:2009) to be both more likely to participate in applied STEM CTE and more likely to complete more units. Finally, when exploring female students and students with IEPs, we found that these students were more likely to participate in applied STEM CTE, but were not more likely to complete more units. Conclusions: A first implication from these findings is that it appears the national efforts and sentiments around increasing high schoolers' participation in CTE course-taking have taken hold. Second, it appears there may be a specific role for states as they look to grow participation in applied STEM CTE—and CTE in general. Finally, additional focus needs to be placed on increasing CTE participation for underrepresented students.